BASIC GLOBAL RESEARCH TRENDS ON CADASTRE: A BIBLIOMETRIC ANALYSIS - Erkhinova Maftuna Lukhmon khizi (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract. In this article, particularly the global research status of cadastre was evaluated by using bibliometric analysis. This article is based on the analysis of research topics, scientific production, collaboration among countries and authors. Furthermore, most cited papers on cadastre research which obtained from database of Scopus during the time period from 2012 to 2023. Land use changes, as a practical and advanced space exploration technology, offered a lot of valuable data about the earth surface for global analysis. This study focuses on analyzing various aspects of research. These include scientific outputs, research directions, source journals, author performance and contributions, the distribution of research across countries/territories and institutions, collaboration patterns, and temporal trends in keyword usage.